Women’s Knowledge and Attitude toward Reproductive Health after an Educational Intervention - Tetti Solehati; Cecep Eli Kosasih; Ermiati E (Journal of Maternity Care and Reproductive Health, 2018)
The risk of health problems especially reproductive health issues is threaten adult women. This may because of inadequate knowledge of reproductive health, and less support related to their attitude. This research aimed to assess the effect of health education on adult women’s knowledge and attitude related to health prevention in reproductive health. This study was a quantitative study using quasi-experiment research design with pre and posttest with one group design. 15 adult women involved in this study that were chosen using the accidental sampling technique. The data were gathered in two steps which were before and after an educational intervention. Respondents filled in a valid instrument about health prevention actions in women’s reproductive health. The data were analyzed using SPSS software version 22.0, the paired t-test applied in this study. The results showed that the average of respondents’ knowledge levels before intervention were 48, and then increased to 78 after intervention (p = 0.000). The average attitude score was changed from 3.14 to 3.69 after intervention (p = 0.005). There is an effect of an educational intervention in improving women’s knowledge and attitude. The recommendation, a regular schedule of health education interventions is required by women to prevent or to overcome reproductive health issues. Keywords: Attitude, Education, Knowledge, Women